Microestructuras en los autos sacramentales de José de Valdivielso: un camino hacia Calderón - Enrique Duarte (Les Cahiers de Framespa)
The author of this article examines some microstructures used by José de Valdivielso in his sacramental plays. In this research, the concept « composition paradigm » is employed. The main studied paradigms are the announcements, spells, tales, songs (with the important role Music has in the sacramental plays) and topoi, those common places that readers used to this kind of allegorical theatre finds in different authors.